Optimalisasi Pemanfaatan Aplikasi Mobile JKN Pada Masyarakat Di Kelurahan Sanggrahan - Nurhayati, Asti (STIKES Yayasan RS.Dr.Soetomo, 2022)
This community service activity is carried out to increase the knowledge and understanding of the Sanggrahan Village community regarding the use of the JKN mobile application. As well as providing an understanding of the features contained in the JKN mobile application. The implementation period of activities with a period of 1 month. After the counseling, this community service activity is expected to increase the knowledge and understanding of Sanggrahan Village residents regarding the use of the JKN mobile application. Object of this community service activity is the community in Sanggrahan Village, Grogol District, Sukoharjo Regency, Central Java. Method used is counseling and explaining the features contained in the JKN mobile application. The education provided is about the national health insurance program (JKN) and the use of the JKN mobile application to make it easier for the public to access national health insurance services (JKN). Outreach results can be measured through a questionnaire that will be given to participants at the time of counseling in Sanggrahan Village. Results of this community service showed that 59% of the community felt helped by the JKN mobile application. It is easier for the public to access health services by utilizing the features in the JKN mobile application. For the level of user satisfaction, 51% of the public expressed satisfaction in using the JKN mobile application. Conclusion This Community Service Activity really helps the community in optimizing the use of the JKN mobile application